Impact evaluation of a maternal and child cash transfer intervention, integrated with nutrition, early childhood development, and agriculture messaging (MAZIKO-IE): A study protocol for a cluster-randomised controlled trial - The Maziko Trial Team; Gelli, Aulo; Duchoslav, Jan; Gladstone, Melissa; Gilligan, Daniel O.; Katundu, Mangani; Maleta, Ken; Quisumbing, Agnes R.; Bliznashka, Lilia; Ahun, Marilyn (Springer, 2024)
Children in Malawi face high rates of malnutrition and are at risk of not reaching their developmental potential. Community-based childcare centres (CBCCs) can be cost-effective platforms for scaling-up early childhood development (ECD) and nutrition social behaviour change (SBC) interventions. However, evidence also suggests potential synergies from coupling nutrition SBC with cash transfers (CT), given that rural households in Malawi face high levels of poverty and recurring extreme lean season food-security shocks. The Maziko trial is aimed at evaluating the effectiveness and cost-effectiveness of using CBCCs and parenting care groups as platforms to improve maternal diets and child nutrition and development by providing nutrition-sensitive SBC and CT intervention packages in communities already receiving a standard of care Government SBC program.